Innovators in Digital News - Kung, Lucy (RISJ Challenges, 2015)
News organisations are struggling with technology transitions and fearful for their future. Yet some organisations are succeeding. Why are organisations such as Vice and BuzzFeed investing in journalism and why are pedigree journalists joining them? Why are news organisations making journalists redundant but recruiting technologists? Why does everyone seem to be embracing native advertising? Why are some news organisations more innovative than others? Drawing on extensive first-hand research this book explains how different international media organisations approach digital news and pinpoints the common organisational factors that help build their success.